Innovative Transformation of the Volga Region's Economic Space - Dmitry L. NAPOLSKIKH (Communications of International Proceedings, 2020)
The article deals with the analysis of economic, financial, scientific and technological conditions for regulating clustering processes and innovative development of the Volga region. The subject of the study is innovative transformation of the regional economic space. The aim of the work is to analyze the processes of innovative transformation of the economic systems of the Volga region regions. The scientific novelty of the work lies in the method of complex analysis of the potential of innovative development of regions. The proposed methodology includes both indicators for assessing the factors of formation of a new innovative economy, and indicators of the effectiveness of innovative development, which form the technological and resource reserve for further economic development of the region. The advantage of using proposed methodology is the possibility of separating for each economic district and interregional cluster the leading regions, which acts as the center of innovative transformation of the economic space of the neighboring regions. It is concluded that the key regions for innovative transformation are Samara region and Republic of Tatarstan.
Keywords: Clusters; Institutional Development; Innovative Potential; Scientific and Technical Development.